Parts-per-Billion Detection of Hydrogen Sulfide via Cavity Ring-Down Spectroscopy - Wei Xu; Xuejun Wang; Lei Zhao; Jun Zou; Bing Chen (Photonics)
Rapid and precise detection of hydrogen sulfide (H2S) at trace levels is critical for industrial safety and environmental air quality monitoring, yet existing methods often struggle with cost, speed, or sensitivity. A cost-effective cavity ring-down spectroscopy (CRDS) analyzer is presented, incorporating a novel digital locking circuit for sequential laser-cavity mode matching. This system demonstrates rapid and precise hydrogen sulfide (H2S) detection capability at parts-per-billion (ppb) concentration levels. Compared to traditional wavelength meters, our system delivers a 140-fold improvement in frequency interval precision (0.07 MHz, 0.027% relative uncertainty). Allan variance analysis under vacuum conditions demonstrates a sensitivity limit of 3 × 10−12 cm−1 at a 60-s averaging time. Validated through calibrated gas dilution tests, the analyzer detects a 4 ppb H2S absorption signal with a signal-to-noise ratio (SNR) > 6, establishing a 2 ppb detection limit (3σ criterion). This innovative approach meets stringent industrial and environmental requirements, offering a significant advancement in trace gas-sensing technology.